Modified slump test a non-expert method for assessing debris flow potential - Alcala, Mark Paulo S.D.; Luy, Kristina U.; Zarco, Mark Albert H.; Tan Tian, Jaylord U. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
This study is a non-expert method in assessing debris flow potential through slump test Soil samples that pass through sieve no. 40, for instance, silt type were used to determine how these materials will slump. Samples that have greater particle diameter like sand are the limitations for this study. The procedure that was used was a modified slump test where a pineapple can and soil samples were used instead of the usual laboratory cone mold and concrete for a slump test. Since cans are cheap and are readily available, these can easily be used by Local Government Units (LGUs). The relationship between the slump height and the moisture content of the sample was determined From this, a plot of the yield stress versus moisture content was made and a breaking point was determined which is 46% in which this moisture content had caused the material to flow and behave like fluid. The infiltration rate of the soil sample was also determined. The researchers conducted the modified infiltration rate test in order to determine the rate on how water is absorbed by the soil by using the USDA infiltration test as a guide. This was done with varying moisture content from10 to 60 percent with 10 percent moisture content increments. The results showed as the moisture content increases, the infiltration rate decreases with respect to time. This study can be used in determining how soil behaves in a debris flow.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Debris avalanches